Strategy for Implementing Man-Hour Based Remuneration and Release Maintenance for Aircraft Engineer Performance at Aviation Facilities Calibration Center - Pujiati, Herni; Budi, Yohanes; Yosepha, Sri Yanthy; Cahaya, Yohanes Ferry (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
The aviation industry has high demands in terms of safety and operational efficiency. Aircraft engineers play a crucial role in ensuring the airworthiness of aircraft through strict and structured maintenance. However, the remuneration system implemented at the Aviation Facilities Calibration Center (BBKFP) is still based on flight hours, which is considered less appropriate to the workload and responsibilities of engineers. Therefore, this study aims to analyze the strategy for implementing a remuneration system based on man hours maintenance and Release Maintenance in improving the performance of aircraft engineers at BBKFP. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and document studies. The results of the study indicate that a remuneration system based on man hours has the potential to increase engineer motivation and productivity, but needs to be supported by a structured performance evaluation system to avoid a decrease in the quality of work. In addition, work-life balance factors, training support, and fair incentive mechanisms are important aspects in implementing this policy. Based on these findings, it is recommended that BBKFP adopt a remuneration system that is not only based on man hours, but also considers aspects of work quality and effectiveness. In addition, periodic monitoring and evaluation are needed to ensure that this policy can be implemented optimally without reducing flight safety and efficiency standards